The impact of organizational learning on relationship orientation, logistics service effectiveness and performance - Panayides, Photis (My University, 2007)
The paper investigates the effects of organizational learning on inter-firm relationship orientation in the logistics service provider–client interaction. A conceptual model is developed and four research hypotheses are empirically examined using structural equation modelling. The data were collected via a survey of Hong Kong based logistics service providers. The results indicate that organisational learning has a positive influence on relationship orientation as well as on the improvement of logistics service effectiveness and firm performance. Theoretical, managerial and research implications are discussed
Keywords: Marketing--Management; Logistics; Organizational learning; Relationship marketing